L’espace anxiogène dans Les Misérables de Victor Hugo - Bogusławska, Aleksandra (Romanica Silesiana)
The topic of this article is an analysis of space presented in Victor Hugo’s novel Les Misérables. The specific emphasis is put on the novel’s attributes which provoke fear in the reader. Apart from characteristic features of other subgenres of popular novel Les Misérables includes a significant number of gothic novel’s elements and consequently fits squarely in literary horror fiction. The majority of these characteristics is related to a presentation of anxiogenic space which is an embelmatic example of gothic genre. It manifests itself thorough an existence in a novel of gloomy, terrifying, death- related places namely, Waterloo battlefield, old Vaugirard cemetary, the areas of Chelles forest. Several buildings depicted by Victor Hugo for instance the ruins of Gorbeau and Petit-Picpus-Saint-Antoine monastery resemble black dwellings (demeures noires) – due to their image and their narrative functions in the text – which are currently demonstarted in Gothic fiction novels. Key words: gothic novel, black novel, literary horror fiction, anxiogenic space, fear, teror, fright, black dwelling